Laterally Ordered Sub‐10 nm Features Obtained From Directed Self‐Assembly of Si‐Containing Block Copolymer Thin Films. Issue 48 (5th November 2015) - Rho, Yecheol; Aissou, Karim; Mumtaz, Muhammad; Kwon, Wonsang; Pécastaings, Gilles; Mocuta, Cristian; Stanecu, Stefan; Cloutet, Eric; Brochon, Cyril; Fleury, Guillaume; Hadziioannou, Georges
Abstract : Laterally ordered sub‐10 nm features are produced from the directed self‐assembly of poly(1, 1‐dimethyl silacyclobutane)‐ block ‐poly(methyl methacrylate) (PDMSB‐ b ‐PMMA) thin films on sinusoidal azobenzene‐containing patterns. The use of sinusoidal surface relief grating enables the formation of very large grain areas (over several µm 2 ) consisting of out‐of‐plane PMMA cylinders.